Pyrethroid-based hair preparations- What a pharmacist needs to know? - Bašić, Jasmina; Amidžić, Bisa; Rajić, Jelena; Antonijević, Biljana (Archives of Pharmacy, 2022)
Pyrethroid-based preparations are available in the form of: anti-lice shampoos, sprays, gels and lotions to remove lice and nits. Pyrethrin is a natural mixture of chemicals, present in flowers from the chrysanthemum family. Pyrethroids are chemicals produced with a structure very similar to pyrethrins, but more toxic to both insects and mammals, and last longer in the environment. An analysis of 19 anti-lice preparations available in the pharmacies showed that 9 preparations contained, as an active component, one of the pyrethroid substances: permethrin, tetramethrin and phenothrin. Although the toxic potential of this group of compounds is low, side effects are possible, most often as a result of acute toxicity, which can manifest itself through disorders of the nervous system or allergic reactions. Another important mechanism of action are skin and respiratory system allergies. The most common side effects from the spectrum of allergic reactions are pruritus, skin irritation, erythema, tingling, blisters on the skin and eczematous changes, dermatitis with miliary red papules, eye irritation. Signs of neurotoxicity are associated with acute (inhalation and dermal) exposure: abnormal facial sensations (paresthesia), dizziness, headache, nausea, loss of appetite, blurred vision and chest tightness, lethargy and muscle fasciculations. Although they are recommended for oral scabies and lice, pyrethrin and pyrethroid-based preparations rarely cause side effects. It is important that the pharmacist warns and informs patients about the proper use of these preparations, especially due to more frequent use in the pediatric population showing increased sensitivity.